Keunikan Budaya dan Keindahan Alam sebagai Citra Destinasi Bali menurut Wisatawan Australia Lanjut Usia - I Gusti Bagus Rai Utama (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
In recent years, many has begun to doubt the continued existence of Bali’s nature and culture in shaping its destination image. The current research was conducted to confirm the existence of culture and nature as the determining factors of Bali’s image as a tourism destination by selecting elderly Australian tourists as respondents, because this group tends to be more loyal and have longer average length of stay compared to other groups of tourists. This research aims to confirmatively answer the existence of Bali’s culture and nature as the destination’s identity and tourism image. The two main research questions are (1) what is the relationship between motivation, destination creation, and destination identity in forming the destination image of Bali? (2) how is the structural model of Bali’s destination image according to elderly Australian tourists? This research was conducting using survey method and quantitative analysis technique, involving 160 elderly Australian tourists. Findings from SEM analysis indicate that internal motivation influences destination image, while destination identity influences destination image, and destination creation also influences destination image. The research concludes that according to elderly Australian tourists, Bali’s culture and nature are remain strong factors in forming the island’s destination image.